Ekstraksi dan Studi Sifat Optik Pewarna Alami untuk Aplikasi Dye-Sensitized Solar Cell - Musyarofah, Musyarofah; Prayitno, Budi; Fauziyah , Nur Aini; Nuraini , Umi; Puspitasari, Nurrisma (LPPM ITK, 2023)
Extraction and study of the optical properties of natural dyes from several plant parts such as leaves, flowers, tubers, and fruits have been carried out using a simple maceration method and UV-Vis absorption characterization. The samples were divided into several groups in this study, namely the flower group (Tagetes sp., Paeonia sp., Centaure sp., Chrysanthemum sp., Carthamus tinctorius, Gomphrena globosa, Myosotis sylvatica, Lavandula sp., Clitoria ternatea, Matricaria chamomilla, Hibiscus sabdariffa, and Rosa sp.); the leaf group (Mangifera indica, Moringa oleifera, Graptophyllum pictum, Spinacia oleracea, Citrus hystrix, and Terminalia sp.); and the tuber and fruit group (Solanum lycopersicum, Cucurbita moschata, Garcinia mangostana, Curcuma longa, Beta vulgaris, and Caessapina sp.). The extract of natural dyes was successfully produced using a low-cost and simple extraction approach via dehydration, immersion for 2×24 hours in ethanol, and followed by filtration. The optical properties of the dyes in UV and visible light range were observed using a UV-Vis spectrophotometer in the wavelength of 400-700 nm. The absorption behaviour showed dominant peaks at different wavelengths for each group. Potentially, to do a combination of dyes (co-sensitization: using more than a dye with different absorption spectra to achieve a panchromatic response) to widen the wavelength absorption for dye-sensitized solar cell (DSSC) applications.